SnO2-based dye-sensitized hybrid solar cells exhibiting near unity absorbed photon-to-electron conversion efficiency. - Snaith, H; Ducati, C (2010)
Improving the solar light harvesting and photon-to-electron conversion efficiency for hybrid, organic-inorganic photovoltaics are critical challenges. Titania based solid-state hybrid solar cells are moderately efficient at converting visible photons to electrons, but major electrical losses still remain. A material based paradigm shift is required to dramatically enhance the performance of these devices. Here, we present an investigation into solid-state dye-sensitized solar cells (SDSCs) incorporating a molecular hole-transporter and mesoporous tin oxide electrodes, in place of titania usually employed. We investigate the influence of treating the surface of the SnO(2) with different oxides and find that MgO "passivated" SnO(2) electrodes demonstrate an unprecedented absorbed photon-to-electron conversion efficiency of near unity across a broad spectral range. A dual surface treatment of TiO(2) followed by MgO enables tuning of the solar cell photovoltage, fill factor, and efficiency with visible light absorbing cells delivering 3% solar-to-electrical full sun power conversion efficiency.